2016
DOI: 10.1002/2016je005048
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anomalies concentrated near and within Mercury's impact basins: Early mapping and interpretation

Abstract: Ninety‐five low‐altitude passes of MErcury Surface, Space ENvironment, GEochemistry, and Ranging magnetometer data from February, March, and April of 2015 have been applied to produce an approximate map of the crustal magnetic field at a constant altitude of 40 km covering latitudes of 35°–75°N and longitudes of 90°–270°E. Anomalies are concentrated near and within the Caloris impact basin. A smaller concentration occurs over and around Sobkou Planitia and an associated older large impact basin. The strongest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Instead, it possesses very localized magnetic field anomalies. Such anomalies are also found on the Earth (e.g., Lesur et al, ), the Moon (e.g., Purucker & Nicholas, ), and Mercury (Hood, ; Johnson et al, ), but the Martian anomalies are 1 or 2 orders of magnitude more intense than on these bodies.…”
Section: Introductionmentioning
confidence: 89%
“…Instead, it possesses very localized magnetic field anomalies. Such anomalies are also found on the Earth (e.g., Lesur et al, ), the Moon (e.g., Purucker & Nicholas, ), and Mercury (Hood, ; Johnson et al, ), but the Martian anomalies are 1 or 2 orders of magnitude more intense than on these bodies.…”
Section: Introductionmentioning
confidence: 89%
“…A valuable data set for investigating crustal magnetism on Mercury was obtained by the NASA MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) Discovery mission during the final year of its existence (Johnson et al, ). Altitude‐normalized maps of the crustal field covering part of one side of the planet (mainly 90 ∘ E to 270 ∘ E and 35 ∘ N to 75 ∘ N) have previously been constructed from low‐altitude magnetometer data using an equivalent source dipole (ESD) technique (Hood, , ; hereafter H15 and H16). Results showed that the strongest crustal field anomalies in this region are concentrated around and within the 1,550‐km‐diameter Caloris impact basin.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal depth of the array for a given spacing of the dipoles is determined by repeating the inversion procedure until a minimum root‐mean‐square (RMS) deviation of the model radial field values from the observed radial field measurements is obtained. For example, a depth of about 20 km for a dipole array with a horizontal spacing of 1°in latitude and 2°in longitude centered at 55°N latitude was found to be optimal using MESSENGER data [ Hood , ]. The derived depth of this equivalent source representation does not imply that the true sources are at this depth.…”
Section: Mapping Methods and Resultsmentioning
confidence: 99%